250 MHz Rapid Scan Cross Loop Resonator - Buchanan, Laura A. (Appl Magn Reson, 2018)
A 25 mm diameter 250 MHz crossed-loop resonator was designed for rapid scan electron paramagnetic resonance imaging. It has a saddle coil for the driven resonator and a fine wire, loop gap resonator for the sample resonator. There is good separation of E and B fields and high isolation between the two resonators, permitting a wide range of sample types to be measured. Applications to imaging of nitroxide, trityl, and LiPc samples illustrate the utility of the resonator. Using this resonator and a trityl sample the signal-to-noise of a rapid scan absorption spectrum is about 20 times higher than for a first-derivative CW spectrum.